Stimulation of Basal Secretion in the Treatment of Dry Eye Syndrome - L. I. Uchakova; S. V. Balalin; V. L. Zagrebin (Oftalʹmologiâ)
The aim is to evaluate the effectiveness of Stillavit in the treatment of dry eye syndrome (DES) and its effect on the density of conjunctival goblet cells and the functional parameters of tear production. Methods. There were analyzed treatment results of 18 patients (36 eyes) with DES at the age of 48 to 80 years (average 60.6 ± 1.3 years) including 17 women and 1 male before and after 1 and 3 months after Stillavit prescription. In all patients in addition to a standard ophthalmological examination the results of Schirmer I, Norn, as well as the LIPCOF test were evaluated and the density of conjunctival goblet cells was examined. Results. After 1 and 3 months there was a significant improvement in the results of the Norn test: from 5.17 ± 0.22 seconds to 7.18 ± 0.17 seconds which indicated an increase in the stability of the tear film. After 3 months there was a significant increase in the density of conjunctival goblet cells, improvement in the Schirmer sample: from 9.26 ± 0.89 to 11.7 ± 0.6 mm (t = 2.28, p < 0.05) and LIPCOF test (t = 2.18, p < 0.05) which indicated an increase in tear production and a significant decrease in the inflammatory process and edema of the conjunctiva. Conclusion. Treatment of DES with the use of Stillavit leads after 3 months to a significant increase in the density of conjunctival goblet cells, increases tear production and stability of the tear film.